A Review on Valorization of Coal Fly Ash into High-Purity Silica: Extraction Methods, Applications, and Future Perspectives - Devi Lestari; Imas Masriah (Research in Chemical Engineering, 2026)
Coal fly ash (CFA), a by-product of coal combustion, contains high silica (SiO₂) content and is continuously generated, making it a promising secondary source of silica. Efficient extraction of silica from CFA can support sustainable material utilization, reduce industrial waste, and align with circular economy principles. This review analyzes recent advances in CFA-derived silica, focusing on extraction techniques, structural characteristics, applications, sustainability, and future prospects. Techniques examined include alkaline leaching, acid dissolution, alkali fusion, sol–gel processing, hydrothermal activation, and emerging biological and process-intensified methods such as ultrasonic treatment and ZnO sintering. Key factors such as CFA composition, Si/Al ratio, and amorphous content are discussed for their influence on extraction efficiency. Recovery efficiencies of CFA-derived silica vary from 38% to over 93%, with cascaded processes achieving purities up to 99%. Structural forms range from amorphous nanoparticles to ordered mesoporous frameworks, enabling applications in construction, catalysis, environmental remediation, energy storage, and biomedicine. Life cycle assessments show that CFA valorization significantly reduces CO₂ emissions compared to conventional quartz-based silica production. Limitations include feedstock heterogeneity, reagent consumption, and economic feasibility. CFA-derived silica offers a sustainable route for industrial waste mitigation while providing high-purity silica for advanced applications. Future research should focus on greener hybrid extraction methods, process standardization, and application-driven material design, supported by regulatory and cross-sector collaboration.